2014
DOI: 10.1371/journal.pone.0099730
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of C10orf10 and Its Prognostic Significance in Human Breast Cancer

Abstract: Breast cancer is a common malignant tumor, which severely threatens the health of women with an increasing incidence in many countries. Here, we identified C10orf10 as a novel differentially expression gene using expression microarray screening. The expression analysis indicated that C10orf10 was frequently decreased in human breast cancers compared to noncancerous breast tissues (81/95, P = 0.0063). Kaplan-Meier analysis indicated that patients with low C10orf10 expression showed a poorer prognosis both in mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…In the present study, we also identified IGF2 as a differentially expressed gene between tumor and non-tumor ovarian tissues (19), and we confirmed its expression in normal, corresponding non-cancerous and cancerous ovarian tissues by reverse transcription-polymerase chain reaction (RT-PCR), real-time quantitative PCR (RT-qPCR), western blotting and IHC. Furthermore, the prognostic significance of IGF2 expression was analyzed in human ovarian cancers.…”
Section: Introductionsupporting
confidence: 72%
“…In the present study, we also identified IGF2 as a differentially expressed gene between tumor and non-tumor ovarian tissues (19), and we confirmed its expression in normal, corresponding non-cancerous and cancerous ovarian tissues by reverse transcription-polymerase chain reaction (RT-PCR), real-time quantitative PCR (RT-qPCR), western blotting and IHC. Furthermore, the prognostic significance of IGF2 expression was analyzed in human ovarian cancers.…”
Section: Introductionsupporting
confidence: 72%
“…C10orf10 plays a role in cell cycle regulation and DNA repair 19 . Lower expression levels correlate with worse BC outcomes 20 and higher levels are linked to glioma proliferation 21 . These ndings suggest C10orf10's relevance not only to gliomas but also to the prognosis of CD-related BC.…”
Section: Discussionmentioning
confidence: 99%
“…DEPP was first identified as a protein related to progesterone in endometrial stromal cells [27,28]. Accumulating evidence has shown that DEPP is positively linked with breast cancer and has a connection with energy deprivation and ionizing radiation [29][30][31]. Specifically, levels of DEPP are elevated in response to starvation and oxidative stress, which in turn promoted reactive oxygen species (ROS) accumulation, resulting in mitochondrial dysfunction and apoptosis [32].…”
Section: Discussionmentioning
confidence: 99%